About Voltage Total Harmonic Distortion for Single- and Three-Phase Multilevel Inverters - Ruderman, Alex (IEEE transactions on industrial electronics (1982), 2015)
Many recent multilevel inverter papers end up with voltage total harmonic distortion (THD) values obtained from numerical voltage spectrum calculations (measurements). Motivated by IEEE Standard 519, a part of the multilevel research community uses a limited harmonic count to evaluate the multilevel voltage quality. First, this causes significant voltage THD underestimation, particularly for relatively high frequency PWM. Second, for a three-phase star-connected balanced load with an isolated neutral and phase symmetric modulation strategy, the calculated load line and phase voltage THD become different. However, simple considerations show that line and phase voltage THDs are essentially the same in this case. It may be difficult to judge about the multilevel voltage quality given a numerically calculated (measured) voltage THD value that may be subject to computation errors. Presented are simple smooth hyperbolic voltage THD upper and lower bound approximations for single- and three-phase inverters with nearest synchronous switching. They are valid for arbitrary modulation indices and uniformly distributed level counts and may practically serve as good reference values.